What Drives Low-Human Development in South Bangka Regency? Integrating with ARIMA Forecasting - Samsuddin, M. Afdal; Putra, Agung Rizki; Rahmani, Zikri (Trunojoyo University of Madura, 2024)
This research aims to analyze the increase in the components of the human development index (HDI) in South Bangka Regency, namely (1) Life Expectancy (LE), (2) and Mean Years of Schooling (MYS), (3) Per Capita Expenditure (PCE). This research also aims to test the autoregressive integrated moving average (ARIMA) time series model to predict the three HDI components. The data in this study uses secondary data obtained from various sources from 2011 to 2022. The results of our study show that, Life expectancy is influenced by access to clean water and the number of doctors in South Bangka Regency, the mean years of schooling are influenced by the number of elementary school teachers and the education budget, and the increase in per capita expenditure is influenced by the increase in government spending. The prediction results show that this model is accurate enough for forecasting. The research results show that the ARIMA model has the best performance for predicting LE, MYS, and PCE where the LE ARIMA model is (2,2,2), the MYS ARIMA model is (3,1,1), and the ARIMA PKE model is (2,1,2).